FinTech, BigTech and Banks : Digitalisation and its Impact on Banking Business Models - Hari Krishna, B.; Arun Kumar, A. (Indian Journal of Finance, 2020)
This is a book review of Fintech, BigTech and Banks : Digitalisation and its Impact on Banking Business Models by Alessandra Tanda and Cristiana - Maria Schena. Both the authors’ effort in framing the title itself attracts the attention of the readers. The book highlights the important phase of digitalization of financial markets and services, thereby converting them into the digital economy. The book highlights micro to macro level of discussion about both the fintech and bigtech firms. Further, it elaborates on the operational and regulatory challenges faced by the financial institutions while adapting themselves to the new technologies with a sole aim to meet the customers’ expectations in terms of varied innovative products and services. It explains the strategic approach of the large banks by investing and partnering with fintech and bigtech firms with a motto of enhanced customer services by offering innovative financial products and services. The challenges faced by small banks in the competitive market are also discussed, and finally, the book synthesizes about the regulatory framework and the digitalization of financial products and services.